Selection of dispute resolution methods: factor analysis approach - Chong, Heap Yih; Zin, R. (Emerald, 2012)
Purpose: The purpose of this research is to discover the behavior of dispute resolution in the Malaysian construction industry by analyzing factors that affect the selection of dispute resolution methods using factor analysis approach. Design/methodology/approach: Preliminary interviews and a questionnaire survey were conducted. Dispute resolution methods were grouped and discussed together, based on the similarity of their characteristics, and used for the questionnaire survey. This research approach is different from the earlier studies that mostly focused on a single dispute resolution method. The data were further analyzed with factor analysis. This improved the data interpretation. Findings: Seven latent factors were extracted and revealed that the contractors and developers preferred alternative dispute resolution (ADR). However, the appreciation of the outcomes of ADR was perceived to be very low. Arbitration and litigation were in part accepted and agreed upon by the respondents. Originality/value: The combined results from the literature review on the stages of dispute resolution and the latent factors affecting the selection of dispute resolution methods could assist in decision making. The selection of ADR or non‐ADR itself is not a major issue; rather, there is a concern for increased efficiency and an appreciation of the methods in the construction industry are more demanding.